Edaravone dexborneol alleviates neuronal senescence injury by mitigating the innate immune response - Jingxian Sun; Mingsheng Yu; Haowei Li; Lin Ma (Tissue and Cell, 2027)

In-situ evolution of biochar structure along with carbon/nitrogen migration during biomass oxy-fuel combustion - Dawei Guo; Shaozeng Sun; Dongdong Feng; Haowei Sun; Yijun Zhao; Qirong Wu; Shuangji Yu (Fuel, 2026)

Strain-Dominated Pathways of Floating Marine Debris in Xiamen Bay Identified Using Lagrangian Coherent Structures - Haowei Sun; Wenxin Lin; Xiao-Hai Yan; Jianwei Lin; Zishen Li; Lijing Gao; Yuwu Jiang; Xin Zhang (Ocean Modelling, 2026)

Machine learning models unravel contrasting enrichment of uranium and arsenic in groundwater from the Songnen Basin, China - Haowei Sun; Zhipeng Gao; Wengeng Cao; Xiaosi Su; Huaming Guo (Journal of Hydrology, 2026)

Large-scale implementation of greenhouse medium-regulated solar interfacial evaporation - Chuanshuai Dong; Jing Huang; Haowei Sun; Hui Kong; Lizhi Zhang (Chemical Engineering Journal, 2026)

Sulfur-based mixotrophic denitrification with PCL/corncob for low C/N mariculture wastewater: Kinetics, microbial mechanism, machine learning optimization and continuous-flow validation - Liwei Wang; Haowei Wen; Xiefa Song; Weimin Yu; Teng Ma; Zuoliang Sun; Zheng Zhou; Huilin Wang; Dengpan Dong; Xueshu Han; Meng Li (Aquaculture, 2026)

Comparing the Effect of Supervised and Unsupervised High-Intensity Circuit Training on Physical Fitness and Psychological Responses in Young Inactive Females - Haowei Zhang; Borui Zhang; Chen Zheng; Eric Tsz-Chun Poon; Qianwen Liao; Fenghua Sun (Journal of Science in Sport and Exercise, 2026)

Influence of sand particle size on fire suppression performance of oil well fires in desert - Zhen Lou; Guangchao Sun; Kai Wang; Xinyu Chang; Hengjie Qin; Sen Li; Nian Jiang; Haowei Yao (Process Safety and Environmental Protection, 2026)

Zein-coated versus zein-inserted kaempferol liposomes: enhancing bitterness masking, stability, and bioaccessibility - Haowei Yang; Xiufang Bi; Ruifeng Ying; Khizar Hayat; Xiaohong Sun; Chunlei Ni; Quan "Sophia" He; Meigui Huang (Food Chemistry, 2026)

Data-driven optimization of coagulation process for high-organic sea cucumber aquaculture wastewater: Interpretable ML modeling and robust TSS soft sensor development - Liwei Wang; Haowei Wen; Xiang Feng; Xiefa Song; Zuoliang Sun; Huilin Wang; Dengpan Dong; Meng Li (Aquacultural Engineering, 2026)

Enhancing winter wheat yield estimation by synergizing UAV remote sensing and a hybrid PROSAIL–AquaCrop data assimilation framework - Yang Xu; Xiaobo Gu; Jingya Liu; Ximeng Li; Gengmin Jiang; Zhikai Cheng; Haowei Yin; Tongtong Zhao; Yadan Du; Shikun Sun; Huanjie Cai (Agricultural and Forest Meteorology, 2026)

Impacts of climate and land use changes on the cultivable area for winter wheat and their economic benefits in China - Haowei Sun; Li Wang (Land Use Policy, 2026)

The diurnal variation of rainfall events with different durations during the flood season in Guangdong, China - Cuicui Gao; Haowei Chen; Haiheng Wang; Yuezhen Deng; Liangju Zhao; Guorong Sun; Fangjin Xiao (Meteorology and Atmospheric Physics, 2026)

Construction of 1D–2D/0D Co3O4/LaF3 heterojunction for integrated enhancement of capacity, rate capability, and voltage window in aqueous supercapacitors - Yin Sun; Haowei Wang; Maosheng Ge; Shuhuang Tan; Banglin Deng; Kun Zhang; Haibang Zhang; Shoujun Zhang; Chengqi Sun; Xinyu Wang (Chemical Engineering Journal, 2026)

Oxy-fuel combustion kinetics of biomass: insights from multi-heating-rate experiments and kinetic analysis - Dawei Guo; Dongdong Feng; Haowei Sun; Yijun Zhao; Shaozeng Sun (Bioresource Technology, 2026)

The effects of β-lactoglobulin-puerarin interaction on the properties of protein hydrogels - Peng Man; Lina Sun; Jinghua Pei; Xiue Han; Huajiang Zhang; Haowei Ren (International Dairy Journal, 2026)

Understanding α-amanitin hepatotoxicity: Mechanisms from cellular models - Haowei Wang; Xiaoxing Zhang; Xiaodong Li; Xinyu Zhang; Teng Sun; Yuqian Wang; Xinyu Zheng; Xinminxiu Zhao; Jianxing Liu; Shangwen Wang; Xiaofeng Zeng (Toxicology, 2025)

Suppression performances of electric vehicle fires by fine water mist in an underground garage - Zhen Lou; Guangchao Sun; Guoqiang Qin; Hengjie Qin; Huaitao Song; Liang Wang; Jianhua Fu; Yiru Lu; Haowei Yao (Process Safety and Environmental Protection, 2025)

Microwave-assisted one-pot synthesis of hierarchical MnCO3/NiO heterojunction with superior energy storage performance for aqueous supercapacitor - Yin Sun; Gaoyong Zhang; Shuhuang Tan; Haowei Wang; Yichen Liu; Chengqi Sun; Banglin Deng; Kun Zhang; Zhaoqing Gao; Naibao Huang (Chemical Engineering Journal, 2025)

Impact of Pacific decadal Oscillation on the extremely cold event frequency in the Taiwan Strait - Yimin Zhang; Yuwu Jiang; Enhui Liao; Wenfang Lu; Yaozhao Zhong; Haowei Sun; Xing Liu; Zhaoyun Wang; Xiaoran Shi (Climate Dynamics, 2025)

Viral Diversity Mediates Carbon Allocation for Ecosystem Multifunctionality Across Biomes - Sen Li; Weigen Huang; Bin Ma; Longlong Xia; Han Hu; Yishen Sun; Haowei Ni; Mengting Maggie Yuan; Jizhong Zhou; Jiabao Zhang; Yuting Liang (Global Change Biology, 2025)
Viral diversity is essential for regulating the stability of ecosystem function by modulating the biochemical cycles via alterations in the survival and metabolic processes of host organisms. However, how viral survival strategies impact ecosystem function remains unresolved. Here, we analyzed 1824 metagenomes from soils across eight biomes, revealing that lytic viruses constituted a dominant proportion (88%) of the viral communities, with Siphoviridae (35.34%) being the most abundant lytic viral group. Viral communities significantly impacted soil organic carbon dynamics, while ecosystem multifunctionality was notably influenced by microbial necromass carbon, microbial biomass carbon, and various environmental factors. Microbial carbon use efficiency was the primary driver of ecosystem multifunctionality, with significant modulation by lytic and lysogenic viral communities, and lytic viruses contributed more directly to ecosystem multifunctionality (3%) compared to lysogenic viruses (1%). Our study underscores the pivotal role of viral communities, particularly lytic viruses, in shaping global carbon dynamics and ecosystem function, thereby providing a novel framework for future carbon management.

GO-SELEX-enhanced dual-recognition sensor for highly specific detection of azamethiphos - Lingjun Geng; Jingcheng Huang; Haowei Dong; Haifang Wang; Rui Xu; Zhiping Yu; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Journal of Hazardous Materials, 2025)

Dual-recognition strategy sensor based on GO-SELEX aptamer screening for high-specificity identification of fenthion and its major metabolites in vegetables - Lingjun Geng; Haowei Dong; Qingxia Han; Xue Huang; Jingcheng Huang; Haifang Wang; Rui Xu; Jicheng Zhao; Zhouping Wang; Shijia Wu; Ibrahim A. Darwish; Yemin Guo; et al. (Food Bioscience, 2025)

Multi-routine-data driven spatio-temporal short-term predictions for surface ozone in China - Canju Zheng; Hengqing Shen; Jianan Sun; Guangliang Liu; Haowei Cao; Jie Zhang; Xiang Gong; Da Xu (Air Quality, Atmosphere & Health, 2025)

A Novel Rock Damping Ratio and Damping Coefficient Based on Linear Energy Damping Law - Haowei Yang; Bing Sun; Jie Cui; Sheng Zeng; Yi Shan (Rock Mechanics and Rock Engineering, 2025)

Influence of fine water mist on gas generation of lithium-ion batteries packs fire in an energy-storage cabin - Zhen Lou; Junqi Huang; Guangchao Sun; Hengjie Qin; Huaitao Song; Zhuang Zhang; Haowei Yao (Process Safety and Environmental Protection, 2025)

Microwave-assisted synthesis of a β-cyclodextrin/TEMPO-oxidized cellulose/Fe3O4 adsorbent for Pb and Cu remediation in soil - Siqi Wang; Mengning Wang; Haowei Wu; Xiaoqi Sun; Zonghao Dong; Wei Peng; Bo Zhang; Chen Cai; Jianhua Qu (Journal of Cleaner Production, 2025)

Effects of nighttime LED supplementary lighting on growth, ovarian development and serum hormone levels of Acipenser gueldenstaedtii in flow-through system - Haowei Cai; Qiming Zhou; Ying Liu; He Ma; Yan Sun; Yuqiang Li; Boyun Jiang; Meijia Li; Shijian Xu; Maninder Meenu; Lei Zhang (Aquaculture, 2025)

Optimizing aflatoxin B1 detection in peanut kernels through deep modular combination optimization algorithm: A deep learning approach to quality evaluation of postharvest nuts - Zhen Guo; Haifang Wang; Haowei Dong; Lianming Xia; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Postharvest Biology and Technology, 2025)

Preparation strategy of molecularly imprinted polymers adsorbent based on multifunctional carrier for precise identification and enrichment of fenthion - Lingjun Geng; Jingjing Liu; Jingcheng Huang; Haifang Wang; Peisen Li; Rui Xu; Chengqiang Li; Haowei Dong; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Food Chemistry, 2025)

Novel time-resolved fluorescent-based multiplex immunochromatography test strip for simultaneous detection of pesticides in vegetables - Zhengtao Li; Haowei Dong; Haifang Wang; Donghan Li; Shuxian Zhou; Shengxi Zhai; Jingcheng Huang; Rui Xu; Wenping Zhao; Mohamed Bedair M. Ahmed; Gili Bisker; Xia Sun; et al. (Food Chemistry, 2025)

Strip biosensors based on broad-spectrum aptamers and cationic polymers for the on-site rapid detection of tetracycline antibiotics residues in milk - Shengxi Zhai; Mengyuan Bai; Fengling Yue; Haifang Wang; Jingcheng Huang; Haowei Dong; Bei Yuan; Zhengtao Li; Pengwei Zhang; Mingxin Zhao; Yemin Guo; Xia Sun; et al. (Food Chemistry, 2025)

Origin of the late Carboniferous Karamaili Granite Belt in Eastern Junggar, Northwest China: Zircon U-Pb and trace element constraints - Qiwei Wang; Bowen Zhang; Jiangang Ding; Xinzhong Zhan; Yaxiaer Yalikun; Mayila Aishan; Xiang Wei; Yacong Wang; Haowei Peng; Yafei Sun; Yunlong Sun (International Geology Review, 2025)

Self-Organized Criticality and b-Value Characteristics of Acoustic Emission of Rocks Under Different Stress Paths - Bing Sun; Yi Yan; Shanyong Wang; Chunming Qi; Haowei Yang; Sheng Zeng (Rock Mechanics and Rock Engineering, 2025)

Quantitative trait loci mapping for agronomic and leaf chemistry traits using high density linkage map in flue-cured tobacco (Nicotiana tabacum L.) - Ke Zhang; Chunqiong Wang; Dan Chen; Xiaowei Zhang; Haowei Sun; Jie Long; Haiyan Li; Jieyun Cai; Dan Li; Jiwu Zhang; Jinchu Yang; Dexin Liu; et al. (Euphytica, 2025)

Cavity-modulated visualization of dual magnetic coupling behavior for multifunctional Co/DMAOP composites - Man Li; Xiao Li; Jieyan Zhang; Haowei Zhou; Zhenfa Yu; Chao Li; Moustafa Adel Darwish; Tao Zhou; Shi-Kuan Sun; Di Zhou (Chemical Engineering Journal, 2024)

Effects of water table depth variations on canopy transpiration from Mongolian pine plantations in arid ecosystems - Yanwen Bai; Ziyan Li; Junjie Dai; Katsutoshi Seki; Ying Zhao; Haowei Sun; Yanhui Wang; Zhenxia Ji; Li Wang (Journal of Hydrology, 2024)

Enhanced detection of Aspergillus flavus in peanut kernels using a multi-scale attention transformer (MSAT): Advancements in food safety and contamination analysis - Zhen Guo; Jing Zhang; Haifang Wang; Haowei Dong; Shiling Li; Xijun Shao; Jingcheng Huang; Xiang Yin; Qi Zhang; Yemin Guo; Xia Sun; Ibrahim Darwish (International Journal of Food Microbiology, 2024)

Oxygen vacancy-rich β-Bi2O3/Bi2O2SiO3 Z-Scheme heterojunction: A strategy to enhance visible light-driven photocatalytic removal of ARB and ARGs - Zhengkun Yu; Yunlei Zhou; Haowei Zhang; Miao Zhang; Shuqi Gong; Huanshun Yin; Tianyi Sun (Environmental Pollution, 2024)

Novel electrochemiluminescence sensing platform for ultrasensitive detection of malathion residue in tea based on SiO2NSs doped Luminol/AgNPs as a signal amplification strategy - Peisen Li; Jiashuai Sun; Haifang Wang; Jingcheng Huang; Lingjun Geng; Haowei Dong; Donghan Li; Chengqiang Li; Mingxuan Fang; Xin Zhang; Lubin Song; Yemin Guo; et al. (Journal of Hazardous Materials, 2024)

Multifunctional nanoenzyme lateral flow immunoassay strip for rapid and ultrasensitive detection of carbofuran in vegetables - Shengxi Zhai; Haowei Dong; Haifang Wang; Jingcheng Huang; Donghan Li; Zhengtao Li; Zhaopeng Li; Peisen Li; Pengwei Zhang; Mingxin Zhao; Xia Sun; Yemin Guo (Journal of Hazardous Materials, 2024)

Preparation of dual recognition adsorbents based on molecularly imprinted polymers and aptamer for highly sensitive recognition and enrichment of ochratoxin A - Lingjun Geng; Jingjing Liu; Wenbin Zhang; Haifang Wang; Jingcheng Huang; Guangxian Wang; Mengjiao Hu; Haowei Dong; Jiashuai Sun; Mingxuan Fang; Yemin Guo; Xia Sun (Journal of Hazardous Materials, 2024)

Novel cross-linkable fluorescent probe with oriented antibody to enhance lateral immunoassay strip for the detection of acetamiprid - Donghan Li; Haowei Dong; Zhengtao Li; Haifang Wang; Jiashuai Sun; Jingcheng Huang; Peisen Li; Shuxian Zhou; Shengxi Zhai; Mingxin Zhao; Xia Sun; Yemin Guo (Journal of Hazardous Materials, 2024)

Accessing color-tunable afterglows from single conventional chromophore-based polysaccharide films through palette strategy - Tianjie Wang; Zhengshuo Wang; Zijin Li; Zheng Chen; Haowei Sun; Hua Yuan; Hanlin Ou; Xiaoyu Huang; Yeqiang Tan (Chemical Engineering Journal, 2024)

Combination of Capture-SELEX and Post-SELEX for procymidone-specific aptamer selection and broad-specificity aptamer discovery, and development of aptamer-based lateral flow assay - Haowei Dong; Haifang Wang; Zhen Guo; Jingcheng Huang; Pengwei Zhang; Yemin Guo; Xia Sun (Analytica Chimica Acta, 2024)

Dual-aspect attention spatial-spectral transformer and hyperspectral imaging: A novel approach to detecting Aspergillus flavus contamination in peanut kernels - Zhen Guo; Jing Zhang; Haifang Wang; Shiling Li; Xijun Shao; Haowei Dong; Jiashuai Sun; Lingjun Geng; Qi Zhang; Yemin Guo; Xia Sun; Lianming Xia; et al. (Postharvest Biology and Technology, 2024)

Experimental and numerical investigation on heat transfer performance of a single-tube six-fin tube evaporator - Zhili Sun; Kexin Meng; Hongyu Liu; Chunwei Xu; Qiang Zhou; Qianqian Wang; Lei Yan; Haowei Peng (International Journal of Refrigeration, 2024)

Intrinsic microbial temperature sensitivity and soil organic carbon decomposition in response to climate change - Sen Li; Manuel Delgado‐Baquerizo; Jixian Ding; Han Hu; Weigen Huang; Yishen Sun; Haowei Ni; Yanyun Kuang; Mengting Maggie Yuan; Jizhong Zhou; Jiabao Zhang; Yuting Liang (Global Change Biology, 2024)
Soil microbes are essential for regulating carbon stocks under climate change. However, the uncertainty surrounding how microbial temperature responses control carbon losses under warming conditions highlights a significant gap in our climate change models. To address this issue, we conducted a fine‐scale analysis of soil organic carbon composition under different temperature gradients and characterized the corresponding microbial growth and physiology across various paddy soils spanning 4000 km in China. Our results showed that warming altered the composition of organic matter, resulting in a reduction in carbohydrates of approximately 0.026% to 0.030% from humid subtropical regions to humid continental regions. These changes were attributed to a decrease in the proportion of cold‐preferring bacteria, leading to significant soil carbon losses. Our findings suggest that intrinsic microbial temperature sensitivity plays a crucial role in determining the rate of soil organic carbon decomposition, providing insights into the temperature limitations faced by microbial activities and their impact on soil carbon‐climate feedback.

Experimental analysis of a CO2 closed heat pump drying system combined with rotary dehumidification for drying banana slices drying - Zhili Sun; Qianqian Wang; Yingying Yuan; Dandan Wang; Qiang Zhou; Chunwei Xu; Kexin Meng; Haowei Peng; Lei Yan; Rui Jin; Lei Li; Haowei Liu; et al. (International Journal of Refrigeration, 2024)

Combined BiLSTM and ARIMA models in middle- and long-term polar motion prediction - Kehao Yu; Haowei Shi; Mengqi Sun; Lihua Li; Shuhui Li; Honglei Yang; Erhu Wei (Studia Geophysica et Geodaetica, 2024)

A dual-mode biosensor featuring single-atom Fe nanozyme for multi-pesticide detection in vegetables - Guangxian Wang; Jing Liu; Haowei Dong; Lingjun Geng; Jiashuai Sun; Jingjing Liu; Jiwei Dong; Yemin Guo; Xia Sun (Food Chemistry, 2024)

Effects of LED spectra on the growth and physiological mechanism of juvenile Sebastes schlegelii. Part I: Growth, feeding and digestion and metabolism - Songtao Liu; Haowei Cai; Ying Liu; Yining Zhang; Yingying Fang; Fei Sun; Yanling Wu; Xin Li; Likang Lv; Qian Zhang; He Ma (Aquaculture, 2024)

Neonicotinoids: Advances in hazards of residues, screening of aptamers and design of aptasensors - Jingcheng Huang; Haifang Wang; Haowei Dong; Mengyue Liu; Lingjun Geng; Jiashuai Sun; Zhen Guo; Rui Xu; Giovanna Marrazza; Xia Sun; Yemin Guo (Trends in Food Science & Technology, 2024)

Impact of climate change on wheat production in China - Haowei Sun; Yanhui Wang; Li Wang (European Journal of Agronomy, 2024)

Multiple spatial scales of bacterial and fungal structural and functional traits affect carbon mineralization - Zhiyuan Ma; Shuo Jiao; Kaikai Zheng; Haowei Ni; Dong Li; Na Zhang; Yunfeng Yang; Jizhong Zhou; Bo Sun; Yuting Liang (Molecular Ecology, 2024)
Studying the functional heterogeneity of soil microorganisms at different spatial scales and linking it to soil carbon mineralization is crucial for predicting the response of soil carbon stability to environmental changes and human disturbance. Here, a total of 429 soil samples were collected from typical paddy fields in China, and the bacterial and fungal communities as well as functional genes related to carbon mineralization in the soil were analysed using MiSeq sequencing and GeoChip gene microarray technology. We postulate that CO 2 emissions resulting from bacterial and fungal carbon mineralization are contingent upon their respective carbon consumption strategies, which rely on the regulation of interactions between biodiversity and functional genes. Our results showed that the spatial turnover of the fungal community was 2–4 times that of the bacterial community from hundreds of meters to thousands of kilometres. The effect of spatial scale exerted a greater impact on the composition rather than the functional characteristics of the microbial community. Furthermore, based on the establishment of functional networks at different spatial scales, we observed that both bacteria and fungi within the top 10 taxa associated with carbon mineralization exhibited a prevalence of generalist species at the regional scale. This study emphasizes the significance of spatial scaling patterns in soil bacterial and fungal carbon degradation functions, deepening our understanding of how the relationship between microbial decomposers and soil heterogeneity impacts carbon mineralization and subsequent greenhouse gas emissions.

Improving food security and farmland carbon sequestration in China through enhanced rock weathering: Field evidence and potential assessment in different humid regions - Fuxing Guo; Haowei Sun; Jing Yang; Linsen Zhang; Yan Mu; Yanping Wang; Fuyong Wu (Science of The Total Environment, 2023)

Variability of volume transport in the Taiwan Strait and its response to tropical MJO convection: A numerical approach - Haowei Sun; Zhaoyun Chen; Zhonghua Zhao; Mengdi Xu; Yimin Zhang; Xiao-Hai Yan; Xueding Li; Yuwu Jiang (Ocean Modelling, 2023)

Vitrification induces a focused spindle pole in mouse MI oocytes - Yaoyao Guo; Haowei Sun; Hui Chen; Gongshe Yang; Jialun Wang; Zhengjun Qi; Weijun Pang; Guiyan Chu; Lei Gao (Theriogenology, 2023)

UV-triggered carrier transport regulation of fibrous NiO/SnO2 heterostructures for triethylamine detection - Huiyi Zhao; Jianhua Sun; Jinmei Liu; Haowei Zhang; Huaguang He; Xuemei Liu; Dankui Liao; Zhangfa Tong; Lixia Sun (Chemical Engineering Journal, 2023)

Strontium isotopes as tracers for water-rocks interactions of groundwater to delineate iodine enrichment in aquifer of Datong Basin, northern China - Kun Qian; Haowei Sun; Junxia Li; Xianjun Xie (Applied Geochemistry, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

Influence of nitrogen addition on the functional diversity and biomass of fine roots in warm-temperate and subtropical forests - Wen Li; Wenqian Wang; Ruomin Sun; Mengke Li; Haowei Liu; Yifei Shi; Dandan Zhu; Junyong Li; Lei Ma; Shenglei Fu (Forest Ecology and Management, 2023)

Spatio-temporal distribution patterns and quantitative detection of aflatoxin B1 and total aflatoxin in peanut kernels explored by short-wave infrared hyperspectral imaging - Zhen Guo; Jing Zhang; Haowei Dong; Jiashuai Sun; Jingcheng Huang; Shiling Li; Chengye Ma; Yemin Guo; Xia Sun (Food Chemistry, 2023)

Control strategy study for a heat pipe cooled nuclear reactor - Xianshan Zhang; Haowei Sun; Jiajun Huang; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2023)

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

Driving factor analysis and dynamic forecast of industrial carbon emissions in resource-dependent cities: a case study of Ordos, China - Jing Li; Zhuoya Ma; Haowei Sun; Wenhui Chen (Environmental Science and Pollution Research, 2023)

Ru360 protects against vitrification-induced oocyte meiotic defects by restoring mitochondrial function - Haowei Sun; Yaoyao Guo; Ruochun Yu; Jialun Wang; Youxue Liu; Hui Chen; Weijun Pang; Gongshe Yang; Guiyan Chu; Lei Gao (Theriogenology, 2023)

Changes in per capita wheat production in China in the context of climate change and population growth - Haowei Sun; Jinghan Ma; Li Wang (Food Security, 2023)

Multiplex strategy electrochemical platform based on self-assembly dual-site DNA tetrahedral scaffold for one-step detection of diazinon and profenofos - Guanjie Wang; Jiashuai Sun; Baoxin Li; Fukai Guan; Jingcheng Huang; Haowei Dong; Jiali Zhang; Jie Han; Zheng Shen; Deyan Xu; Xia Sun; Yemin Guo; et al. (Science of The Total Environment, 2023)

Interaction between N6-methyladenosine (m6A) modification and environmental chemical-induced diseases in various organ systems - Xiaofang Zhu; Haowei Fu; Jiahui Sun; Qian Xu (Chemico-Biological Interactions, 2023)

m6A contributes to a pro-survival state in GC-2 cells by facilitating DNA damage repair: Novel perspectives on the mechanism underlying DEHP genotoxicity in male germ cells - Haowei Fu; Xiaofang Zhu; Qiannan Di; Jiahui Sun; Qianqian Jiang; Qian Xu (Science of The Total Environment, 2023)

Effects of forest age on soil erosion and nutrient loss in Dianchi watershed, China - Wenxian Sun; Xiaoyin Niu; Yongping Wang; Xianwei Yin; Haowei Teng; Peiling Gao; Aiju Liu (Environmental Monitoring and Assessment, 2023)

Damage Constitutive and Failure Prediction of Artificial Single-Joint Sandstone Based on Acoustic Emission - Bing Sun; Haowei Yang; Sheng Zeng; Yu Luo (Geotechnical and Geological Engineering, 2022)

Response of sedimentation rate to environmental evolution in Da River Reservoir in Southwest China - Wenxian Sun; Zike Zhou; Xianwei Yin; Yongping Wang; Haowei Teng; Aiju Liu; Yanfei Ma; Xiaoyin Niu (Environmental Science and Pollution Research, 2022)

Preparation and Evaluation of Novel Supersaturated Solid Dispersion of Magnolol - Jing Zhao; Pan Gao; Chengqiao Mu; Jingqi Ning; Wenbin Deng; Dongxu Ji; Haowei Sun; Xiangrong Zhang; Xinggang Yang (AAPS PharmSciTech, 2022)

Comparison of transpiration of differently aged apple orchards on the Loess Plateau of China at multiple temporal scales - Rui Zhang; Di Wang; Haowei Sun; Chaohui Wei; Li Wang (Hydrological Sciences Journal, 2021)

A latitudinal gradient of microbial β‐diversity in continental paddy soils - Xian Xiao; Na Zhang; Haowei Ni; Yunfeng Yang; Jizhong Zhou; Bo Sun; Yuting Liang (Global Ecology and Biogeography, 2021)
Aim The β‐diversity of plants and animals generally decreases with increasing latitudes. Here, we tested whether this relationship also holds for soil microbes at both functional and taxonomic levels. Location China. Time period Between June and October 2013. Major taxa studied Soil archaea, bacteria, and functional genes. Methods We used a spatially explicit ‘L‐shaped’ sampling strategy in 39 paddy fields in China to study the pattern of soil microbial β‐diversity (i.e., species turnover, β z ) across a latitudinal gradient (19.75° N to 47.58° N), with 11 soil samples taken within a 100 m × 100 m plot from each field. Archaeal and bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using Illumina MiSeq; microbial functional genes involved in C/N/P/S cycling were detected by GeoChip. Results We showed that the microbial β‐diversity varied considerably across taxonomic and functional groups. For both soil microbial communities and functional genes, β‐diversity decreased significantly along elevated latitudes at the continental scale. Woesearchaeota of archaeal communities, Bacteroidetes of bacterial communities, and the functional genes involved in methane production displayed the greatest decreases. Both mean temperature during the growing season of rice plants and paddy soil heterogeneity contributed to the latitudinal patterns. Further analyses indicated that temperature was more important than soil heterogeneity in driving the β‐diversity of microbial communities and functional genes. Main conclusions These results highlight the importance of temperature‐driven soil microbial β‐diversity and suggest the potential to predict the changes of microbial diversity with climate change.

Thermal Extrusion 3D Printing for the Fabrication of Puerarin Immediate-Release Tablets - Pingfei Li; Haoyue Jia; Shiming Zhang; Yining Yang; Haowei Sun; Haoyu Wang; Weisan Pan; Fei Yin; Xinggang Yang (AAPS PharmSciTech, 2020)

Microbial responses to inorganic nutrient amendment overridden by warming: Consequences on soil carbon stability - Mengmeng Wang; Junjun Ding; Bo Sun; Junyu Zhang; Kristen N. Wyckoff; Haowei Yue; Mengxin Zhao; Yuting Liang; Xiaoyue Wang; Chongqing Wen; Jizhong Zhou; Yunfeng Yang (Environmental Microbiology, 2018)
Summary Eutrophication and climate warming, induced by anthropogenic activities, are simultaneously occurring worldwide and jointly affecting soil carbon stability. Therefore, it is of great interest to examine whether and how they interactively affect soil microbial community, a major soil carbon driver. Here, we showed that climate warming, simulated by southward transferring Mollisol soil in agricultural ecosystems from the cold temperate climate zone (N) to warm temperate climate (C) and subtropical climate zone (S), decreased soil organic matter (SOM) by 6%–12%. In contrast, amendment with nitrogen, phosphorus and potassium enhanced plant biomass by 97% and SOM by 6% at the N site, thus stimulating copiotrophic taxa but reducing oligotrophic taxa in relative abundance. However, microbial responses to nutrient amendment were overridden by soil transfer in that nutrient amendment had little effect at the C site but increased recalcitrant carbon‐degrading fungal Agaricomycetes and Microbotryomycetes taxa derived from Basidiomycota by 4‐17 folds and recalcitrant carbon‐degrading genes by 23%–40% at the S site, implying a possible priming effect. Consequently, SOM at the S site was not increased by nutrient amendment despite increased plant biomass by 108%. Collectively, we demonstrate that soil transfer to warmer regions overrides microbial responses to nutrient amendment and weakens soil carbon sequestration.

Estimating the parental magma composition and temperature of the Xiaohaizi cumulate-bearing ultramafic rock: Implication for magma evolution of the Tarim large igneous province, northwestern China - Haowei Sun; Yinqi Li; Zilong Li; Siyuan Zou; Charles H. Langmuir; Hanlin Chen; Shufeng Yang; Zhongyuan Ren (Journal of Earth Science, 2016)

Evolution and association analysis of GmCYP78A10 gene with seed size/weight and pod number in soybean - Xiaobo Wang; Yinhui Li; Haowei Zhang; Genlou Sun; Wenming Zhang; Lijuan Qiu (Molecular Biology Reports, 2015)